TIKTOK SEBAGAI MEDIA DAKWAH PERSUASIF: ANALISIS MANAJEMEN TIKTOK RADIO NINA BAYAN SEBAGAI MEDIA PEMBERDAYAAN PEREMPUAN - Purnama, Wahyunia; Ummah, Athik Hidayatul (Mudabbir: Jurnal Manajemen Dakwah, 2024)
This research discusses the management of the TikTok platform as a women's empowerment media that focuses on providing information, educating, and persuading audiences. The positive side of social media contributes as a medium for women's empowerment to voice issues about women. This research aims to analyze Nina Bayan Radio's TikTok management and analyze its opportunities and challenges in the cyber era. This research uses qualitative research with a descriptive approach. The data collection techniques in this research are through observation, interviews and documentation. This research shows two important findings. First, the management of TikTok Radio Nina Bayan applies general management to manage the Gundem Batur Nina program with structured planning, organizing, implementing and monitoring steps. The involvement of the broadcasting team, listener response and online monitoring on TikTok is an integral part of program implementation. Secondly, there is a great opportunity for Radio Nina Bayan to reach a wide audience through the TikTok platform due to the needs of the audience, especially Gen Z. The challenges are limited funding, problems with listeners' response and online monitoring on TikTok. However, the challenges are limited funds, problems in remote areas, and technological management constraints.